Própolis e natação na prevenção da aterogênese e hipertrofia ventricular esquerda de camundongos hipercolesterolêmicos - Silva, Dênis Bueno da (2012)
Inflammatory process, endothelial dysfunction and oxidative stress in cardiovascular environment resulting from dyslipidemia are the conditions that promote and sustain atherosclerosis and cardiac hypertrophy. The present study verified the effect of propolis alone and its association with swimming in dyslipidemia, left ventricular hypertrophy and atherogenesis of hypercholesterolemic mice that were receiving a high-fat diet. 40 LDLr-/- mice, fed with high fat diet (20% total fat, 1.25% cholesterol and 0.5% cholic acid) ad libitum for 75 days, were used in the study. The animals were divided into 4 groups (n=10): hyperlipidic group (HL), sedentary, subjected to aquatic stress; hyperlipidic + swimming group (HL+NAT), submitted to a swimming protocol (1 hour per day, 5 times per week) from the 16th day of the experiment; hyperlipidic + propolis group (HL+PRO), sedentary, submitted to aquatic stress and which received oral propolis (70 µL of the propolis alcoholic extract of 85,71% every weekday) from the 16th day of the experiment; HL+NAT+PRO group, submitted to swimming protocol (1 hour per day, 5 times per week) from the 16th day of the experiment and which received oral propolis (70 µL of the propolis alcoholic extract of 85,71% every weekday) from the 16th day of the experiment. After 75 days of the experiment, the animals were weighed and anesthetized. Blood was collected and laboratory analyzes were performed for total cholesterol and fractions, and triglycerides. After thoracotomy, heart and aorta were removed. The heart was weighed and dissected, the left ventricle isolated, the ratio between the ventricular weight (mg) and the animal weight (g), was calculated and after, it was histologically processed. Ventricle and aorta slides were stained with hematoxina and eosin (HE) and picrosirius red for histological and histochemical analyzes; other slides were treated immunohistochemically with anti-protein proinflammatory CD40L antibodies to evaluate the inflammatory process. The HL animals showed severe dyslipidemia, atherogenesis and left ventricular hypertrophy, associated with a decrease in serum high density lipoprotein (HDL) levels and subsequent development of cardiovascular anti-inflammatory process, characterized by increased expression of CD40L in the left ventricle and aorta. Swimming and propolis separated and / or associated prevented left ventricular hypertrophy (HVE), atherogenesis, ventricular and arterial inflammation, decreasing the expression of CD40L and increased plasma levels of HDL-C. A propolis alone or associated with regular physical activity is beneficial in cardiovascular protection by anti-inflammatory action.